Development and validation of a prognostic nomogram for early-onset colon cancer. Issue 6 (20th June 2019) - Yu, Chaoran; Zhang, Yujie
Abstract : The present study was to develop a prognostic nomogram to predict overall survival (OS) and cancer-specific survival (CSS) in early-onset colon cancer (COCA, age < 50). Patients diagnosed as COCA between 2004 and 2015 were retrieved from the surveillance, epidemiology, and end results (SEER) database. All included patients were assigned into training and validation sets. Univariate and multivariate analysis were used to identify independent prognostic variables for the construction of nomogram. The discrimination and calibration plots were used to measure the accuracy of the nomogram. A total of 11220 patients were included from the SEER database. The nomograms were established based on the variables significantly associated with OS and CSS using cox regression models. Calibration plots indicated that both nomograms in OS and CSS exhibited high correlation to actual observed results. The nomograms also displayed improved discrimination power than tumor-node-metastasis (TNM) stage and SEER stage both in the training and validation sets. The monograms established in the present study provided an alternative tool to both OS and CSS prognostic prediction compared with TNM and SEER stages.